1970
DOI: 10.1128/jb.102.1.6-13.1970
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transport in Mycobacterium smegmatis

Abstract: The transport of D-alanine, D-glutamic acid, and D-valine in Mycobacterium smegmatis was compared quantitatively with that of their L-isomers. It appeared that the uptake of D-alanine was mediated by an active process displaying saturation kinetics characteristic of enzyme function, whereas the uptake of D-glutamic acid was accomplished by a passive process showing diffusion kinetics. Both processes were involved in the uptake of L-alanine, L-glutamic acid, D-valine, and L-valine. D-Valine competed with L-vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…on September 6, 2020 by guest http://aem.asm.org/ Downloaded from that the alanine-permease system is inducible in these bacteria (2) and is in agreement with Yabu's investigations in M. smegmatis (10). Pulse experiments indicated that neither drug interferes with the subsequent induction of the permease system by L-alanine (Table 1); it was also observed that exposing the cells to the drugs during the whole period of induction did not interfere with the induction process.…”
Section: Resultssupporting
confidence: 89%
“…on September 6, 2020 by guest http://aem.asm.org/ Downloaded from that the alanine-permease system is inducible in these bacteria (2) and is in agreement with Yabu's investigations in M. smegmatis (10). Pulse experiments indicated that neither drug interferes with the subsequent induction of the permease system by L-alanine (Table 1); it was also observed that exposing the cells to the drugs during the whole period of induction did not interfere with the induction process.…”
Section: Resultssupporting
confidence: 89%
“…The uptake of L-glutamic acid by C. albidus showed a break in the saturation curve at high amino acid concentrations. Such nonlinear, double reciprocal plots have been found in many bacteria, e.g., Salmonella typhimurium (2), Escherichia coli (17), Pseudomonas aeruginosa (20), Mycobacterium smegmatis (32), Streptococcus faecalis (31) and Streptomyces hydrogenans (13). In general, a particular amino acid was transported by two distinct transport systems: one had a high affinity (Ki) and was very specific for the particular amino acid, whereas the second system had a lower affinity for the amino acid (Ki) and was relatively nonspecific in that it also transported related amino acids (2,7,13,20).…”
Section: Discussionmentioning
confidence: 91%
“…The complex nature of the L-leucine uptake process in both morphological forms of H. capsulatum is indicated by the break in saturation curves at high amino acid concentrations. It was reported that nonlinear, double-reciprocal plots are characteristic of many amino acid transport systems in Pseudomonas aeruginosa (14), and such nonlinearity was discovered in other bacteria and yeasts (3,8,10,11,30). In general, these reports point out that a particular amino acid is transported by two different carrier sites: one has a high affinity (Kmn) and is completely specific for the amino acid, and the other is nonspecific with a low affinity (Kin).…”
Section: Discussionmentioning
confidence: 99%
“…The Km values for the transport system operative at higher external amino acid concentration was theoretically infinite, because the second phase of the double-reciprocal plot passed almost through the origin, indicating that L-leucine was entering the cell by simple diffusion. If a process other than simple diffusion were operative, a second but finite value of the Km should have been observed (3,8,10,30).…”
Section: Fractionmentioning
confidence: 99%